Oral versus intravenous acetaminophen as a constituent of multimodal analgesia after coronary artery bypass graft surgery: A randomized, blinded trial - Sajad Yarahmadi; Behzad Moradi; Rasool Mohammadi; Maryam Saran; Arash Ardalan; Noordin Mohammadi; Tayebeh Cheraghian (Tehran University of Medical Sciences, 2020)
Background & Aim: This trial aimed to compare the pain relief and side effects of Oral Acetaminophen (OA) and Intravenous Acetaminophen (IVA) after CABG surgery. Methods & Materials: This parallel-group, triple-blinded, randomized trial was conducted on 113 CABG patients from September 2017 through February 2018.  The samples were selected through blocked randomization and allocated into two groups using computer-generated. The participants administered 1gr oral (OA group, n=57) or intravenous Acetaminophen (IVA group, n=56) every 6h for the first 24h following surgery; also, pain controlled in both group with Morphine multimodal analgesia strategy. Pain intensity measurement by VAS was followed after extubating the endotracheal tube at the 0, 1, 6, 12, 18 and 24 hours during the rest and deep breathing. The Morphine consumption and the incidence of nausea and vomiting in the first 24h were assessed. Data were analyzed using SPSS software and Chi-square, t-test, mixed ANOVA and ANCOVA test. Results: The pain score in the IVA group was found to be statistically significantly lower than the OA group at rest (P<0.001) and during deep breathing (P<0.001) in the first 24h. There was no statistically significant difference between groups regarding the cumulative Morphine consumption (P=0.056). The use of IVA was associated with a reduction in frequencies of nausea and vomiting incidents (P=0.029). Conclusion: Administration of IVA for the management of postoperative pain in CABG patients significantly reduced pain score and incidence of nausea and vomiting compared to OA. Any reduction in cumulative Morphine consumption did not accompany the lower pain.